Comparative study of three methods for detecting avian leukosis viruses. - Smith, E J (1977)
This investigation was designed to compare detection limits for avian leukosis viruses after infection of chicken fibroblasts with decimal dilutions of Rous-associated virus type 1 (RAV-1). At 5, 9, 14, and 19 days postinfection, cells were examined for group-specific (gs) antigens by microtiter complement-fixation (CF) tests for avian leukosis viruses and by radioimmunoassays (RIA) for the major gs antigen having a molecular weight of 27,000 (p27). Culture fluids, collected at the same time periods, were also assayed for reverse transcriptase activities. We found that minimally infected cultures expressed virus proteins within 9 days postinfection regardless of method used. Although p27 RIA was consistently more sensitive than CF or reverse transcriptase assays, sensitivity was only two- to fivefold greater when concentrated suspensions of RAV-0, RAV-1, and RAV-2 were compared. In terms of infectious units, the lowest detectable virus titer was 6 X 10(3) infectious units as determined by RIA end point dilutions. However, our results led us to conclude that when concentrated cell extracts are tested with hamster antiserum, CF is adequate for detecting infection.